Space—A Virtual Frontier: How to Design and Evaluate a Virtual Reality Experience of the Overview Effect - Stepanova, Ekaterina R.; Quesnel, Denise; Riecke, Bernhard E. (Frontiers in Digital Humanities, 2019)
A select group of people have an amazing opportunity to see the Earth from a unique perspective – in outer space. The effect this experience has on an individual is described as extraordinary and profound, consisting of a cognitive shift in worldview that leads to the understanding of the fragility and vulnerability of the planet, and an increased feeling of connectedness. This experience, termed the ``Overview Effect'', has been reported by many astronauts and space travelers. Its key outcome – an enhanced feeling of interconnectedness – contributes to both one's well-being and the sense of responsibility for the Earth. If this profoundly positive experience can be accessible to more people than just space travelers, a healthier and more caring society may be created, where individuals deeply feel the interconnection of all living beings and responsibility for our collective future. Given virtual reality (VR) technology's potential to induce experiences affecting an immersant in a similar way as a real experience, we see an opportunity to leverage this technology to attempt to elicit the Overview Effect as a virtual experience. Through a virtual installation, the experience could be made accessible to people around the world, and for researchers to study this otherwise rare phenomenon. This article builds the case for VR as a tool for inducing the Overview Effect, and proposes guidelines for: 1) the design of the experience; 2) evaluation methods for assessing if, or to what degree, the experience was achieved. We invite researchers and VR creators to utilize and expand on the guidelines proposed in this paper to design transformative VR experiences that induce positive change, and promote a feeling of connectedness and care for each other, and our Spaceship Earth.